THE CITY OF SALVADOR-BA IN THE CONTEMPORARY CINEMA - Moreira, Tiago de Almeida (2017)
The paper deals with representations about the city of Salvador - BA in contemporary Brazilian cinema, focusing on the public space of the city, its main aspects and socio - spatial contradictions. The inventory of twenty-five films presented contributes to the line of research of the Geographies of Cinema, in structuring in Brazil and in the world, because it deals with the analysis of public space in contemporary Brazilian films, a topic still little explored in Brazil.